Analisis Makna Tradisi Lisan Di Tasikmalaya - Anjani Lintang Pertiwi; Retna Ayu Ratu Gumilang; Winda Murni; Wini Nurlela Sari; Aveny Septi Astriani (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2024)
This research is motivated by the rich and meaningful oral traditions in the city of Tasikmalaya. The aim of this study is to uncover the implicit and explicit meanings behind popular oral traditions in Tasikmalaya. The method employed in this research is the historical method, consisting of heuristics (searching and collecting sources), criticism (internal and external criticism), interpretation, and historiography. The research objects include the Manuscript Amanat Galunggung, the Sawer Tradition, Ambu Hawuk, and the Ki Rangga Gading fairy tale. Data collection was conducted through literature or library studies. The findings of the research reveal that oral traditions such as the Amanat Galunggung Manuscript, Sawer Panganten, Ambu Hawuk, and the Ki Rangga Gading fairy tale provide a profound understanding of moral values, advice or counsel, teachings of life, and the origins of place names in the context of Sundanese culture. This research is beneficial in providing in-depth insights into Sundanese culture, particularly oral traditions. Additionally, it contributes to the fields of knowledge, moral education, and cultural preservation